ANALISIS KETERAMPILAN GURU DALAM MENGGUNAKAN MEDIA PADA PEMBELAJARAN TEMATIK KELAS V SD - Saputri, Septiani; Sabri, Tahmid; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research aims to decide the teacher's competencies in the use of media in the thematic learning of class V SD Negeri 31 West Pontianak. The sub-problem in this study is how is the teacher's method in the usage of media in the thematic learning of class V SD Negeri 31 West Pontianak? and What are the problems confronted via instructors in using media in the thematic learning of category V SD Negeri 31 West Pontianak?. While the technique used is descriptive. The supply of the facts in this learn about was once the fifth grade instructor at SD Negeri 31 West Pontianak. Data collection tools in this study were commentary and interviews. Data analysis in this lookup is using an interactive model with the ranges of statistics reduction, statistics display and the system of drawing conclusions. This lookup suggests (1) the teacher's strategy in the usage of the media and (2) the issues faced by means of the instructor in the use of the media.Keyword : Teacher Skills, Media, Thematic Learning